Pengaruh Celebrity Endorsement Dan Social Media Marketing Terhadap Purchase Intention : Studi Kasus Pada Konsumen Produk 3mongkis Di Kota Bogor - Soedargo, Bayu Prasetyo; Regina, Elsa (Program Vokasi dan LPPM IBI Kesatuan, 2024)
The focus of this research is to evaluate and determine how Celebrity Endorsements and Social Media Marketing influence the desire to purchase 3MONGGIS products. This local fashion product is quite successful in selling its various products. This research falls into the quantitative paradigm category. Sources of data collection include secondary data from the internet as well as journals and primary data collected through searching for main data output by looking for respondents who know the 3MONGGIS brand and distributing general news to predetermined respondents. Taking a sample of 140 people from respondents who were familiar with the 3MONGKIS brand, the purposive sampling method was used for sampling. The research results were evaluated and tested using classical assumptions and hypothesis testing with multiple linear regression analysis using the SPSS program. This study shows that Celebrity Endorsement and Social Media Marketing have a significant influence on Purchase Intention for 3MONGGIS products. Keyword: Celebrity Endorsment, Social Media Marketing, Purchase Intention